The hero [videorecording (DVD)] - Haley, Brett, 1983-; Haley, Brett, 1983-; Elliott, Sam, 1944-; Prepon, Laura, 1980-; Offerman, Nick, 1970- (Lionsgate, 2017)
After he receives a diagnosis of terminal pancreatic cancer, a former Western film star re-evaluates his life.